KEBERLANGSUNGAN USAHA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA SEBELUM DAN SELAMA PANDEMI COVID-19 - Nisa Salsabila; Indayani Indayani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to analyze and compare how business continuity in insurance companies before and during the Covid-19 pandemic using the Springate (S-Score) method. This research employed quantitative descriptive method. The research population is insurance companies listed on the Indonesia Stock Exchange (IDX) in 2016-2021, with a total population of 16 companies. The sampling method used is non-probability sampling using saturated sampling in order to obtain as many as 16 research samples. The research data uses secondary data obtained from the documentation of financial statements found on the Indonesia Stock Exchange (IDX) web page. Analysis of the data used in the form of descriptive statistical tests and paired sample t-test using SPSS 26 data application. The results of the study explain that there are several companies that have been in a healthy condition since the beginning of the 2016-2021 period. There are also companies that have been in bankruptcy since the beginning of the 2016-2021 period, while other companies fluctuate every period. After the paired sample t-test was carried out, the results show that there are differences in the business continuity of insurance companies before and during the Covid-19 pandemic.